(untitled) (TAJ: Journal of Teachers Association, 2009)
Bronchial carcinomas often present with some paraneoplastic features which may present even before the offending tumor has been detected. Hypercalcaemia is one of the most common paraneoplastic sypmtoms. In this prospective cohort study attempts has been made to demonstrate the incidence and pattern of hypercalcaemia in bronchial cancers. The study was undertaken at the Medicine Department of Rajshahi Medical College Hospital, Rajshahi in between July, 2009 to December 2009. In this study hypercalcaemia was found i_n 30.76% cases with anorexia, dyspepsia, nausea, polyuria, polydipsia and constipation being most common features related to it. TAJ 2009; 22(1): 245-247